Czynniki wpływające na skuteczność wywiadu bezpośredniego w badaniach rynkowych - Mocek, Marek; Olejnik, Iwona (The Factors Influencing the Effectiveness of Face-to-Face Interview Method in Market Research, 2006)
The effectiveness of market research is expressed predominantly by the amount of the data collected, their completeness, timeliness of their obtaining, as well as the cost of their acquisition. The method employed most often in market research is the face-to-face interview method and its effectiveness is influenced by, among other factors, the subject scope of the survey, the questionnaire structure, the attitude of the respondent towards the survey, the aspects related with the interviewer as well as the organization and the way of conducting field-based research. The paper discusses the factors regarded as the major determiners of effectiveness in the applications of the face-to-face interview method in market research from respondent's (manager's) point of view. The analysis is based mainly on the results of the empirical research conducted in the Department of Marketing Research of the Poznań University of Economics.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 545-551